Pemanfaatan Tumbuhan Sebagai Penyedap Rasa Alami Oleh Masyarakat Suku Dayak Kanayatn Desa Sebatih Kecamatan Sengah Temila Kabupaten Landak - Mukarlina, Christoper Apri Manangka, Riza Linda (Universitas Tanjungpura, 2017)
Dayak Kanayatn ethnic group in Sebatih village has used plants as ingredient in food inheridited by their ancestors. The study investigated types & parts of plants used as natural flavour. This research was counducted from December 2016 to February 2017 in Sengah Temila using purposive sampling & snow ball. Date ware collected & analysed & the results indicated that ther are 19 species of 14 families used as natural flavour. Ther are 14 species with high freqency of sitasi by 100%, namely: Allium sativum L., Allium cepa L., Phaeomeria speciosa KOORD. & Gnetum gnemon. Besides, ther are 19 species of 14 families used as natural flavour from fruits, flowers, leaves, tubers, steams & seeds.